2019
DOI: 10.1039/c8ra09233h
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a conductive overcoating layer based on hybrid composites to improve the stability of flexible transparent conductive films

Abstract: A protective layer that can be applied on a flat flexible transparent conductive film was prepared by combining silica sol and organic polymer. (3-Glycidyloxypropyl)trimethoxysilane (GPTMS) was used as a precursor for the silica sol, which hydrolyzed under moisture to form silanol groups and selfcondensed to form a sol under acidic conditions. Therefore, the organic polymer used was poly(4styrenesulfonic acid) (PSSA), which is acidic and water-soluble; thus, the silica precursor can form a sol and can cause ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…As shown in Figure 2d, the broad absorption band near 850 nm is attributed to oxidation state of PEDOT, i.e., the single polaron with a positive charge. [42][43][44] By referring to this peak, we found that PEDOT:PSS/salts films showed a much stronger absorption than PEDOT:PSS, corresponding to an enhanced oxidation level (i.e., higher p-doping density) of PEDOT chains. 29 The PEDOT conductivity is primarily dependent on the positive charges located along the polymer backbone.…”
mentioning
confidence: 93%
“…As shown in Figure 2d, the broad absorption band near 850 nm is attributed to oxidation state of PEDOT, i.e., the single polaron with a positive charge. [42][43][44] By referring to this peak, we found that PEDOT:PSS/salts films showed a much stronger absorption than PEDOT:PSS, corresponding to an enhanced oxidation level (i.e., higher p-doping density) of PEDOT chains. 29 The PEDOT conductivity is primarily dependent on the positive charges located along the polymer backbone.…”
mentioning
confidence: 93%
“…With PEGMA as an additive, PEDOT:PSS has flexible properties even after 400% elongation and does not lose the electrical conductivity. However, this electrical conductivity does not last long under ambient conditions because it does not have sufficient environmental stability 31. In the case of PEDOT:P(SS‐ co ‐PEGMA), the relatively hydrophobic PEGMA component is fixed in the P(SS‐ co ‐PEGMA) chain; hence, the polymer is more stable than with PEGMA as an mere additive, as per contact angle analysis (Section S5, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…As far as we have a concern, there is no complete and sufficient mechanism explained on the crystallinity, stretchability and conductivity effects upon secondary doping of PEDOT:PSS. [19][20][21][22] To date, it is still a challenge to fabricate polymer-based strain sensors with desired mechanical properties and sensing performance by intoxicated materials and facile preparation methods.…”
Section: Introductionmentioning
confidence: 99%